RESEARCH ON THE DIRECTIONS OF MONITORING THE USE OF REAL ESTATE IN SETTLEMENTS - Nelin, Ye.; Kasianov, V.; Shterndok, E. (Municipal economy of cities. Series: «Economy science», 2023)
Monitoring real estate assets in settlements is pivotal in effective territorial management. Accurate information on the status and utilisation of these assets is essential for informed decision-making, resource allocation, and the sustainable development of lands within settlements. This research delves into the multifaceted methodologies used to achieve these objectives. The driving force behind this research is the demand for data-driven, geolocation-based decision-making. The precise evaluation of real estate assets within settlements is indispensable for efficient land use planning, infrastructure development, and the prudent management of natural resources. In the ever-evolving urban landscape, comprehending the dynamics of real estate assets is strategically imperative, facilitating optimal resource allocation and sustainable growth. Populated areas often present intricate, multi-layered geographical landscapes. Conventional real estate monitoring methods, such as manual inspections and paper documentation, often fall short of the required timeliness and accuracy for effective management. It is here that modern technologies step in, offering innovative solutions to augment the monitoring process. Geographic Information Systems (GIS) are at the forefront of this transformation. They enable the collection, analysis, and visualisation of spatial data, offering a multidimensional perspective on real estate assets. Through GIS, real-time insights into asset usage, condition, and their impact on the environment become attainable. Utilising GIS empowers decision-makers and stakeholders, aiding informed choices that facilitate sustainable urban planning and development. Furthermore, integrating remote sensing technology elevates the monitoring of real estate assets in settlements. Satellite imagery and aerial photography provide high-resolution data to detect changes and trends. That is particularly valuable for assessing urban expansion, environmental shifts, and the allocation of lands for agriculture, industry, or residential purposes. Ensuring data accuracy, accessibility, and confidentiality is a paramount aspect of efficient real estate monitoring. Advanced data analytics, machine learning algorithms, and blockchain technology can be leveraged to safeguard data integrity, ensure privacy, and enhance the overall quality of information. In summary, research on monitoring the use of real estate assets in settlements stands as a critical field with wide-reaching implications. The amalgamation of GIS, remote sensing technology, and advanced data analytics is reshaping our approach to comprehending, managing, and planning land usage in urban and rural contexts. By harnessing the capabilities of modern technology and data-driven insights, we pave the way for more sustainable and efficient territorial management.